FEMINISTRY PEDAGOGY AS A DIRECTION OF CRITICAL PEDAGOGY - Turchyn, Iryna (Mountain School of Ukrainian Carpaty, 2019)
One has determined the role of the feminist pedagogy in modern science on the basis of the analysis of educators’ views. One has presented a theoretical review of the feminist pedagogy in foreign and Ukrainian scholars’ works, which greatly expands the thorough study of this problem. One has emphasized on the feminist pedagogy as the direction of the critical pedagogy. One has considered the problem of the feminist pedagogy which is relevant, especially due to the Brazilian teacher and philosopher P. Freire’s views. One has determined the role of this pedagogy in his works which occupy a significant place in the research of the pedagogy among the cohort of prominent educators. Having studied the Brazilian educator’s scientific papers, one has found out the equal relationship between a pupil and a teacher, researched in the problem-posing model of education, should be integrated into the feminist direction in the pedagogy. One has noted the importance of student-centrism and democracy in the educational process. One has studied P. Freire’s and I. Shor’s views on sexism during conducting classes. One has analyzed the works of Ukrainian authors (I. Kyzyma and N. Samoilenko) and foreign authors (J. Kenway, L. McClure, D. Macedo, H. Modra, P. Freire, and I. Shor) in the context of studying the feminist pedagogy. The research tasks were to study the feminist pedagogy thoroughly and to emphasize on the full potential of the Brazilian teacher P. Freire’s views concerning this direction of the critical pedagogy. One has used the following theoretical methods: content-analysis, the synthesis of the results of the researched works as well as search and bibliographic ones. One has given the definition of “the feminist pedagogy”, which is the direction of the critical pedagogy, based on the relationship between the sexes in the educational process, in particular, the necessary condition for the change of the attitude to female pupils or students. The relevance of the article lies in the fact of the elaborate analysis of P. Freire’s views and the highlighting the aspects which are relevant in the feminist pedagogy.